Opportunities for Increasing the Efficiency of The Transfer of Innovative Technologies in The Sectors of The Fuel and Energy Complex - Olga PYATAEVA; Alexey ALTUKHOV; Alexander ANISIMOV; Sergey EROKHIN; Lilia MATRAEVA (Communications of International Proceedings, 2021)
The article contains an analysis of technology transfer processes in the energy and oil and gas sectors. A list of legal and regulatory acts regulating these sectors is presented. The authors provide examples of successful practices in transferring innovative technologies in the industries under consideration, including domestic and foreign experiences and present existing instruments for the development of transfer mechanisms based on the reports of sector effectiveness. The authors highlight general trends in the development of these mechanisms, which are relevant for modern Russian and world practice, and emphasize the Russian specificity of technology transfer.
Keywords: Technology Transfer; Energy Sector; Oil And Gas Industry; Innovative Technologies; Legal Acts; Russian Economy.